Between-Group Differences Among Victim Age-based Typologies of Juvenile Sexual Offenders - Short, Jennifer (2018)
Juveniles adjudicated for sexual offenses are often described as homogenous, collectively viewed as inherently dangerous, and subject to specialized legal and clinical interventions. However, empirical studies have identified several typologies suggesting that juveniles adjudicated for sexual offenses are a heterogeneous group with varying degrees of risk and treatment needs. The purpose of this non-experimental between-groups study was to compare family composition, abuse histories, mental health diagnosis, and offense type among a victim age-based typology of juvenile sexual offenders. The theoretical framework that guided this study was developmental-contextual theory. Archival data (N = 105) were collected from Alberta Health Services in Alberta, Canada. Results of chi-square analysis indicated a statistically significant difference among these 2 groups with respect to family composition and offense type. The groups did not differ with respect to abuse histories or mental health diagnosis. Findings may be used to expand the current knowledge base regarding risk factors for youths who offend sexually, to develop preventative programs and treatment programs, to increase community safety, and to reduce the stigma associated with juvenile sexual offending